7. Papillary thyroid cancer in a patient with Morvan's syndrome. Issue 4 (April 2018) - Walker, Susan; Narasimhan, Manisha; Matamala, José Manuel; Dharmadasa, Thanuja; Kiernan, Matthew C.; Huynh, William
Abstract : Background: Morvan's syndrome is a rare disorder, characterized by peripheral nerve hyperexcitability, dysautonomia and encephalopathy with marked insomnia. About three quarters of patients have voltage gated potassium channel (VGKC) antibodies. A significant proportion of patients have associated tumours and the majority of these are thymomas. Introduction: A 53 year-old man presented with a history of pain, cramps and twitching of the muscles of the chest and limbs, insomnia, hyperhidrosis, hypersalivation and cognitive impairment with hallucinations. Examination revealed fasciculations of the proximal upper limbs, piloerection of the forearms and mild postural hypotension. Investigations: The patient underwent a number of electrophysiological studies: (1) EMG demonstrated spontaneous and frequent irregularly occurring neuromyotonic activity as doublet, triplet and multiplet single motor unit discharges firing at a high intraburst frequency (133–200 Hz), consistent with peripheral nerve hyperexcitability. (2) Paired-pulse transcranial magnetic stimulation revealed reduction in the short-interval intracortical inhibition (SICI) suggestive of central hyperexcitability. (3) EEG demonstrated left temporal slowing on an otherwise normal background. (4) autonomic testing showed a generalized sudomotor impairment consistent with autonomic dysfunction. Neuroimaging of the brain with PET demonstrated bilateral temporal lobe hypometabolism. Whole body PET revealed a hypermetabolic thyroid lesion, which was subsequently confirmed histologically to be a multifocal papillary thyroid carcinoma. Discussion: The clinical and electrophysiological presentation was consistent with a diagnosis of Morvan's syndrome in the context of a paraneoplastic phenomenon secondary to papillary thyroid cancer. The patient underwent a thyroidectomy and adjuvant radiotherapy. In addition, monthly intravenous methylprednisolone and intravenous immunoglobulin was instituted. Subsequently, the patient experienced significant symptomatic improvement with resolution of muscle fasciculations and cramps, hyperhidrosis and visual hallucinations. Insomnia and pain although improved did not completely resolve. Conclusion: This case reviews the clinical and neurophysiological findings of Morvan's syndrome. The case adds to the small number of non-thymomatous tumours associated with this syndrome and highlights the importance of a thorough search for malignancy in this clinical context.